FAKTOR LINGKUNGAN DAN MORFOMETRIK UDANG MANTIS (Harpiosquilla raphidea) DI DAERAH INTERTIDAL PERAIRAN PANTAI DESA SULI PULAU AMBON - Tuaputty, Hasan; Kurnia, Tri Santi; Kubangun, Muhammad Tarmizi (Biosel Biology Science and Education, 2023)
Result of biological study and ecology to variatas of morphology of Harpiosquilla raphidea in coastal territorial water of Countryside of Suli of Island Ambon. Result of environmental factor measurement of territorial water of intertidal show the salinitas mean 19,40/00. temperature of temperature means 27,95oC and dissolve Oksigen of mean 6,16 DO mg / L and pH 6,9. Other measurement of length of prawn of Harpiosquilla raphidea found range from 4 cm until 10 cm. Analyse the morfometrit to variatas of prawn of Harpiosquilla raphidea and morphology of colour of husk seen by a white chromatic, tan, white chromatic of black, white chromatic is brass, chocolate chromatic, and black chromatic. The color difference is caused by the presence of astaxanthin pigment, which can absorb color pigments, thus making the shells of the Harpiosquilla raphidea shrimp have various colors. The color and size variation of the shell is also caused by the influence of environmental factors or the substrate as a place of life.